Rituximab monotherapy for splenic marginal zone lymphoma with villous lymphocytes: report on long-term disease control for two patients with recurrence after splenectomy - Debiasi, Márcio; Hehnemann, Marluce; Garicochea, Bernardo (São Paulo Medical Journal, 2010)
CONTEXT: Splenic marginal zone lymphoma (SMZL) is a lymphoproliferative B-cell disorder that has a favorable prognosis, with estimated overall five-year survival of 70%. The majority of symptomatic patients undergo splenectomy, while a few receive first-line chemotherapy, especially with purine analogues. There are no specific treatment guidelines for patients for whom splenectomy fails to provide a cure. It is still unclear whether these patients should undergo cytotoxic chemotherapy, considering they have now a relapsed lymphoma (which is theoretically more aggressive), or whether they should be spared from treatments of greater toxicity, given that their disease usually develops with a more indolent course, even when it recurs. CASE REPORT: Here, we present two patients whose disease recurred after splenectomy and for whom rituximab monotherapy provided satisfactory treatment. From these cases, it can be suggested that postponement of cytotoxic treatments may be possible in at least some situations. It needs to be emphasized that the evidence to support this approach is based only on case reports, since there are no randomized clinical trials on this subject.